BRAIN-BASED LEARNING AS AN APPROACH FOR IMPROVING EDUCATIONAL PRACTICE IN KURDISTAN REGION: AN EMPIRICAL STUDY IN PERSPECTIVE OF EDUCATIONAL PLANNING - Mohammad Sadik (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Brain-based learning refers to teaching methods, lesson designs, and school programs that are based on the latest scientific research about how the brain learns, including such factors as cognitive development-how students learn differently as they grow in age, and become mature socially, emotionally, and cognitively. This study aims mainly at knowing: (1) to what extent educators know the strategy of Brain-Based learning, (2) their ability to apply the strategy, (3) the significant differences between the responses of the educators in both dimensions cognition and application. In order to achieve the above mentioned aims, the study hypothesizes that HO means there is no significant differences in response to educators up on the questionnaire items in both dimensions: cognition and application, collective and individual. The basic conclusion the study arrived at is: Educators do not have any specific knowledge, practice or training in regard to the so called Brain-Based learning strategy. This was obvious through the results, which were at a moderate level (3) in both cognitive and application dimensions. Finally, the study ended with some recommendations for pedagogical implications and some suggestions for further studies.